Interação Biosfera-Atmosfera em área de savana natural na Amazônia: fluxos de energia e CO2 - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2025)
Research conducted in Amazonian savannas has addressed floristic composition, fauna, soil physicochemistry, and the influence of fire on vegetation structure and dynamics. However, there is a notable gap in the biophysical characterization of these ecosystems, particularly due to the lack of micrometeorological studies that are essential for understanding the processes of energy, mass, and momentum exchange between vegetation and the atmosphere. Such studies are also crucial for understanding local climate patterns, which significantly affect vegetation distribution, water resource availability, and carbon dynamics. In this context, the present study was conducted in a natural savanna area located in the municipality of Santarém, Pará, Brazil, with the objective of analyzing energy balance closure and the responses of evapotranspiration and CO₂ fluxes to environmental variables. This was achieved through the analysis of micrometeorological data collected by a tower equipped with an eddy covariance system. The energy balance closure and ET responses during both the rainy and dry seasons were investigated. The results indicated a greater conversion of energy into latent heat during the rainy season and into sensible heat during the dry season, with the energy balance showing a closure rate of over 80%. Hysteresis analysis revealed distinct ET responses throughout the day, influenced by atmospheric conditions and water availability. Additionally, wavelet transform techniques were applied to investigate the correlation between CO₂ concentrations and meteorological variables such as air temperature and wind speed. The results revealed significant correlation cores between CO₂ and temperature, along with intermittent and chaotic patterns in its relationship with wind at the microscale. These findings underscore the importance of considering multiple time scales for understanding gas dispersion and accumulation mechanisms. Finally, the performance of the SiB4 model in simulating seasonal energy fluxes was evaluated, using input data from the MERRA-2 reanalysis, along with soil properties and land cover data. Model validation demonstrated good performance in simulating radiation balance and turbulent fluxes, highlighting its capability to represent observed seasonal variations. Overall, the results reinforce the importance of micrometeorological monitoring and the use of surface models to better understand the physical and biogeochemical processes governing Amazonian savanna ecosystems.
Keywords: Saldo de radiação; Balanço de energia; Histerese; CNPQ:: CIENCIAS AMBIENTAIS